Smart Start: Rituximab, Lenalidomide, and Ibrutinib in Patients With Newly Diagnosed Large B-Cell Lymphoma. Issue 4 (1st February 2023) - Westin, Jason; Davis, R. Eric; Feng, Lei; Hagemeister, Fredrick; Steiner, Raphael; Lee, Hun Ju; Fayad, Luis; Nastoupil, Loretta; Ahmed, Sairah; Rodriguez, Alma; Fanale, Michelle; Samaniego, Felipe; et al.
Abstract : PURPOSE: Chemoimmunotherapy for patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL) is largely unchanged for decades. Both preclinical models and clinical data suggest the combination of lenalidomide and ibrutinib may have synergy in DLBCL, particularly in the non–germinal center B-cell-like subset. METHODS: We enrolled 60 patients with newly diagnosed non–germinal center B-cell-like DLBCL in this investigator-initiated, single-arm phase II trial of rituximab, lenalidomide, and ibrutinib (RLI) with the sequential addition of chemotherapy (ClinicalTrials.gov identifier: NCT02636322 ). Patients were treated with rituximab 375 mg/m 2 intravenous once on day 1, lenalidomide 25 mg once per day on days 1-10, and ibrutinib 560 mg once daily continuously of each 21-day cycle (RLI). After two cycles, standard chemotherapy was added to RLI for six additional cycles. The primary end points were overall response rate (ORR) after two cycles of RLI alone and complete response rate after completion of RLI with chemotherapy. In evaluable samples, circulating tumor DNA and DLBCL90 assays were performed. RESULTS: The median age was 63.5 years (range, 29-83 years) with 28% age 70 years or older. The revised international prognostic index identified 42% as high risk, and 62% were double expressor of MYC and BCL2 protein. The ORR after two cycles of RLI was 86.2%, and the complete response rate at the end of RLI-chemotherapy was 94.5%. With a median follow-up of 31 months, the progression-free survival and overall survival were at 91.3% and 96.6% at 2 years, respectively. CONCLUSION: Smart Start is the first study, to our knowledge, to treat newly diagnosed DLBCL with a targeted therapy combination before chemotherapy. RLI produced a high ORR, and RLI with chemotherapy resulted in durable responses. This establishes the potential for developing biologically driven and noncytotoxic first-line therapies for DLBCL.